Teacher Personality Ethics In The Perspective Of Islamic Educational Philosophy - Utami, Purwani Puji; Ayuningrum, Syamzah; Vioreza, Niken; Nugraheny, Devita Cahyani; Putra, Nanda Lega Jaya (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
This study aims to analyze the personality ethics of teachers in the perspective of Islamic education philosophy. This type of research uses a qualitative approach with a literature study method. Data sources are quoted from credible pages such as Google Scholar and SINTA. Then the data were analyzed and checked for validity through data triangulation. The results of this study concluded that as an educator, it is very necessary to understand the personality that becomes his character. The personality of the educator will become the competence of an educator in building and educating the personality of students through exemplary and authority that emanates from the character and personality of the educator. Thus, educators are not only responsible for educating cognitive and psychomotor competence, but educators are also responsible for shaping the affective of students through exemplary personality. Educators are a reflection and role model in behaving for students.